Effects of a nutrition education intervention on maternal nutrition knowledge, dietary intake and nutritional status among food insecure households in Kenya - Mbogori, Teresia; Murimi, Mary (International Journal Of Community Medicine And Public Health, 2019)
Background: Malnutrition remains a major concern in the developing countries especially in food insecure populations. Maternal nutrition knowledge, among other factors, has been shown to improve nutritional status in children under the age of 5 years. The purpose of this study was to determine the effect of a nutrition education intervention on maternal nutrition knowledge, dietary intake, and nutritional status in Turkana County, Kenya. Methods: Seventy-three mothers/female caretakers with children <5 years old from Nadapal village in Turkana County were included in the study. At baseline, maternal nutritional knowledge, maternal and child nutritional status, and dietary intake were assessed. During the intervention, participants were trained on breastfeeding, complementary feeding, hygiene and sanitation. The intervention was conducted for five days with two- three hour sessions each day. Six months after the intervention, a follow-up was done to assess the effect of the intervention. Results: At baseline, 53% of the women were underweight (BMI<18.5 kg/m2), 24% of the children were stunted, 20.7% wasted, and 28.6% underweight. After the intervention, maternal knowledge on length of breastfeeding and composition of complementary foods improved. There were no significant changes in nutritional status in both women and children after the intervention. Conclusions: Results from this study implied that nutrition education interventions may improve nutrition knowledge of the mothers /female caretakers. However, without provision of food, the effects of the gained nutrition knowledge may not reflect in the dietary intake or nutritional status and therefore future interventions need to include ways to reduce food insecurity.